Kekerasan terhadap Tokoh Perempuan dalam Novel Prasetyane Wanita Karya Tulus Setiyadi Kajian Feminisme - Laily, Siti Nur; Werdingingsih, Yuli Kurniati; Zaidah, Nuning (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2022)
This research contains about violence against female charactersin the novel Prasetyane Wanita by Tulus Setiyadi. This study aims to describeand reveal violence against female characters in the novel Prasetyane Wanitaby Tulus Setiyadi in the study of feminism. With the formulation of the problemhow violence against female characters in the novel Prasetyane Wanitaby Tulus Setiyadi The Study of Feminism.This study uses a qualitative research method because the data are in the form of words, phrases and sentences, the source of the data used is the novel Prasetyane Wanita by Tulus Setiyadi.The data collection technique is in the form of library researchwhich consists of reading techniques and note-taking techniques. Data analysis techniques used in the form of data reduction, data display and data verification.The result of this research is that there are four violences against female characters in the novel Prasetyane Wanita by Tulus Setiyadi. Violence against women figures includes psychological violence against women, physical violence against women, sexual violence against women and sexual violence against women.